Heat pipe based battery thermal management: Evaluating the potential of two novel battery pack integrations. (November 2021) - Jouhara, Hussam; Delpech, Bertrand; Bennett, Robert; Chauhan, Amisha; Khordehgah, Navid; Serey, Nicolas; Lester, Stephen P.
Abstract: Lithium-ion batteries are widely used in high power applications and, with more industries focusing on the electrification of their processes, the need for an effective battery thermal management system is growing. The use of a thermal management system serves multiple purposes such as safeguarding the battery from catastrophic thermal runaway and increasing the lifespan of the battery pack. In the present paper, the thermal management of a sixteen-cell battery module, by two different configurations of a heat pipe based thermal management system, is investigated experimentally. In the first configuration, the module is fixed on top of a single horizontal 'heat mat'. The second configuration consists of the module sandwiched between two vertical heat mats. The comparison of the cooling performances of these two configurations showed their ability to efficiently absorb the heat generated by the cells and maintain their temperatures close to the ideal operating range. During representative cycles of operation, the maximum cell temperature was kept below 28.5 °C and 24.5 °C for the horizontal and vertical heat mat configurations respectively. The cell temperature uniformity across the module stays in a +/-1 °C range, which will reduce cell voltage imbalance, loss of useable capacity and non-uniform ageing. The maximum temperature difference across the height of the cells was 6 °C for the horizontal configuration and 2 °C for the vertical one. The second part of this paper compares the heat removed in both configurations when loaded with a quasi-steady-state heat generation. The third study uses a faster (6C) charge rate during a representative cycle and shows that the maximum temperature stays below 30 °C and 28 °C for the horizontal and vertical configurations respectively.